Bookshelf_ Designing a User-Friendly Library Management Portal with Django (International Journal of Scientific Research in Science and Technology, 2025)
The "Bookshelf: Designing a User-Friendly Library Management Portal with Django" project is dedicated to creating a cutting-edge library management solution. Built on the Django framework, the portal prioritizes user experience by incorporating intuitive features such as secure login, streamlined book addition, and fine management functionalities. Through an accessible and responsive interface, the system aims to optimize library operations, from efficient book inventory management to seamless patron interactions. The project places emphasis on a robust architecture, ensuring scalability, while addressing critical aspects like fines and penalties. Ultimately, the portal seeks to redefine library management, providing a comprehensive, user-friendly, and technologically advanced platform for both library staff and patrons.